Are tibial angles measured with inertial sensors useful surrogates for frontal plane projection angles measured using 2-dimensional video analysis during single leg squat tasks? A reliability and agreement study in elite football (soccer) players - Hughes, T.; Jones, R. K.; Starbuckc, C.; Picot, J.; Sergeant, J. C.; Callaghan, M. J. (Journal of Electromyography and Kinesiology, 2019)
During single leg squats (SLS), tibial angle (TA) quantification using inertial measurement units (IMU) may offer a practical alternative to frontal plane projection angle (FPPA) measurement using 2-dimensional (2D) video analysis. This study determined: (i) the reliability of IMUs and 2D video analysis for TA measurement, and 2D video analysis for FPPA measurement; (ii) the agreement between IMU TA and both 2D video TA and FPPA measurements during single leg squats in elite footballers. 18 players were tested on consecutive days. Absolute TA (ATA) and relative TA (RTA) were measured with IMUs. ATA and FPPA were measured concurrently using 2D video analysis. Within-session reliability for all measurements varied across days (intraclass correlation coefficient (ICC) range = 0.27-0.83, standard error of measurement (SEM) range = 2.12-6.23°, minimal detectable change (MDC) range = 5.87-17.26°). Between-sessions, ATA reliability was good for both systems (ICCs = 0.70-0.74, SEMs = 1.64-7.53°, MDCs = 4.55-7.01°), while IMU RTA and 2D FPPA reliability ranged from poor to good (ICCs = 0.39-0.72, SEMs = 2.60-5.99°, MDCs = 7.20-16.61°). All limits of agreement exceeded a 5° acceptability threshold. Both systems were reliable for between-session ATA, although agreement was poor. IMU RTA and 2D video FPPA reliability was variable. For SLS assessment, IMU derived TAs are not useful surrogates for 2D video FPPA measures in this population.